Computational study of fuel spray structure - Mohd Hilmi, Mohd Zin (2013)
This thesis deals with the study of fuel spray structure via computational (simulation) method. The main objective of this thesis to perform a computational study of pure gasoline fuel sprays structure development where it covers to parts; to determine the pure gasoline fuel spray angle and spray penetration depth characteristics using sing-hole port fuel injector (PFI) and to determine the impact of different injection pressure on the spray structure of pure gasoline fuel. The spray simulations are done completely by using Computational Fluid Dynamics (CFD) ANSYS CFX software with three nozzle tip diameter; 0.2mm, 0.3mm and 0.4mm. The Computational Aided Design (CAD) model for each nozzle was drawn using the SolidWorks software, the nozzle is attached with 110mm bore and 125mm stroke combustion chamber. In the ANSYS CFX software, the ready CAD model is imported into the design modeler and under goes meshing process with fine relevance center, 4 m min size, 4m max face size and 8m max size. There are three types of boundary conditions applied to the meshed geometry model, the first is inlet boundary condition with various injection pressure of 100bar, 150bar, 200bar and 250bar. Opening boundary condition is then place at the combustion chamber with atmospheric pressure value that is 101325Pa and the third boundary condition is wall. The iteration calculation is solved until the convergence approached to the desired residual value and the result is obtained and analyzed. The first comparison made is between penetration depth versus injection pressure and the other is between spray angle versus injection pressure, the results are then compared between nozzle diameter for each injection pressure. The results show that as the injection pressure increased, the penetration depth is also increased as well as the spray angle. The conclusion has shown that the nozzle tip diameter is also effecting the overall spray structure because wider nozzle tip diameter will released more fuel quantity compared to the smaller nozzle tip diameter.